On-farm research manual : (Bureau of Agricultural research, 1990)
This set of books has 11 volumes and the content is devided into 11 modules including Overview and directions of agricultural research; The farming systems approach; Organizing multidisciplinary teams; Feedback mechanisms; Planning on-farm research; Cropping systems research; Crop-livestock systems; Fisheries; Post-production; Pilot production programs; and Data management